2014
DOI: 10.3390/molecules191119066
|View full text |Cite
|
Sign up to set email alerts
|

Pentadecapeptide BPC 157 Enhances the Growth Hormone Receptor Expression in Tendon Fibroblasts

Abstract: BPC 157, a pentadecapeptide derived from human gastric juice, has been demonstrated to promote the healing of different tissues, including skin, muscle, bone, ligament and tendon in many animal studies. However, the underlying mechanism has not been fully clarified. The present study aimed to explore the effect of BPC 157 on tendon fibroblasts isolated from Achilles tendon of male Sprague-Dawley rat. From the result of cDNA microarray analysis, growth hormone receptor was revealed as one of the most abundantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 31 publications
3
77
0
Order By: Relevance
“…BPC 157 reduces high myeloperoxidase (MPO) activity in colonic tissue (Veljaca et al., ), and in particular, heals fistulas (Baric et al., ; Grgic et al., ; Klicek et al., ), rescues failed anastomosis healing (Klicek et al., ; Sever et al., ; Vuksic et al., ), and markedly improves intestinal adaptation following massive bowel resection (Sever et al., ). Studies have shown different molecular mechanisms involved in BPC 157 beneficiary effects (Chang et al., , ; Hsieh et al., ; Huang et al., ). Thus, recently the increased expression and internalization of VEGFR2, and the activation of the VEGFR2‐Akt‐eNOS signaling pathway have been implicated (Hsieh et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BPC 157 reduces high myeloperoxidase (MPO) activity in colonic tissue (Veljaca et al., ), and in particular, heals fistulas (Baric et al., ; Grgic et al., ; Klicek et al., ), rescues failed anastomosis healing (Klicek et al., ; Sever et al., ; Vuksic et al., ), and markedly improves intestinal adaptation following massive bowel resection (Sever et al., ). Studies have shown different molecular mechanisms involved in BPC 157 beneficiary effects (Chang et al., , ; Hsieh et al., ; Huang et al., ). Thus, recently the increased expression and internalization of VEGFR2, and the activation of the VEGFR2‐Akt‐eNOS signaling pathway have been implicated (Hsieh et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, BPC 157 exerts endothelium and mucosal protection in stomach, counteracts variously induced gastrointestinal lesions in different species (Duzel et al., ; Sikiric et al., , , , ), but has not been tested in social insects. Several molecular pathways are discussed as possible targets of BPC 157 (Cesarec et al., ; Chang, Tsai, Hsu, & Pang, ; Chang, Tsai, Lin, Hsu, & Pang, ; Hsieh et al., ; Huang et al., ; Tkalcevic et al., ). Thereby, BPC 157 was considered to be suitable for the extension of the beneficial effect to the entire gastrointestinal tract (Seiwerth et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of action for BPC 157 are not yet fully understood, both in the currently reviewed and other surrounding literature, some light has been shed on a few potential systems involving nitric oxide (NO) (Sikiric et al 2014), the FAK-paxillin pathway (Chang et al 2010), VEGF (Hsieh et al 2017) and the upregulation of growth hormone (receptor) (Chang et al 2014).…”
Section: Prolonged Therapeutic Benefitsmentioning
confidence: 99%
“…In our experimental ulcerative colitis experiments, the peptide enhanced angiogenesis and in tissue extracts we found increased expression of the transcription factor Egr-1 that regulates the expressions of angiogenic growth factors like VEGF, bFGF and PDGF [131]. Furthermore, BPC 157 affects NO-system [133] and several molecular pathways involved in the healing, including growth hormone receptors [134], cell proliferation and migration [135,136], in part by enhanced expression of Egr-1 [131,132].…”
Section: Bpc-157mentioning
confidence: 99%